2013
DOI: 10.4028/www.scientific.net/amm.331.161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Flow Field in the KYF Flotation Cell by CFD

Abstract: The characteristics of flow field in the KYF-0.2 flotation cell are studied by CFD, and PIV test is also carried out to verify CFD simulation results. CFD simulation results show that there is a vortex near the slurry-ward surface of impeller blades in the direction against the rotation direction, there appears the maximum velocity which is higher than the speed at blade tips. Both PIV measuring results and CFD simulation results indicate that high velocity region appears near the exterior of stator blades,whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Their simulation results showed that a high velocity region appears near the stator blades. The PIV results were in good agreement with CFD prediction results . These results were used for the structural design of impellers for KYF flotation cells .…”
Section: Introductionsupporting
confidence: 70%
See 4 more Smart Citations
“…Their simulation results showed that a high velocity region appears near the stator blades. The PIV results were in good agreement with CFD prediction results . These results were used for the structural design of impellers for KYF flotation cells .…”
Section: Introductionsupporting
confidence: 70%
“…There are a few measurement techniques that have been employed to characterize turbulence in flotation cells. These techniques may be divided into single-point and whole flow field methods. The single-point methods give the flow velocity at a given point in the flow field, whereas the whole flow field methods are able to provide the spatial distribution of the flow velocity over a large region of the flow field .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations